(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2016)
هدف هذا البحث إلى دراسة مقدرة نباتي الخروع Ricnuis communis والقصب Phragmites communis على مراكمة عنصري الرصاص Pb والكادميوم Cd المنتشرين طبيعياً على جانبي نهر الرميلة في مدينة جبلة. جمعت العينات النباتية من الأوراق والخشب واللحاء للأنواع النباتية المدروسة، وكذلك جمعت عينات من التربة المحيطة بالنباتات على عمق (0-20 cm). تم أخذ أربع مكررات لكل عينة. تم تقدير تركيزات العناصر المدروسة (Pb,Cd) باستخدام جهاز التحليل الطيفي بالامتصاص الذري (atomic absorption spectrophotometer). أظهرت نتائج البحث أنّ القيمة المتوسطة لمحتوى التربة من كمية الرصاص 61.89 ppm, بينما تراوحت هذه القيمة في أجزاء نبات الخروع بين 4.3-5.81 ppm, و في أجزاء نبات القصب تراوحت بين 1.46-2.32 ppm. وأظهرت نتائج التحليل الإحصائي تفوق أوراق الخروع على خشب الخروع و لحائه في مراكمة الرصاص, و تفوق الخروع على القصب. أما عنصر الكادميوم فقد بلغ متوسط محتوى أتربة الموقع المدروس 3.081 ppm , و كانت في أجزاء نبات الخروع بين 0.031-0.061 ppm, و تراوحت في أجزاء نبات القصب بين 0.031-0.055 ppm. بينت نتائج التحليل الإحصائي أنه لا توجد فروق معنوية بين الخروع و القصب في مراكمة الكادميوم. بناء على ذلك يمكن أن نعدّ الخروع من الأنواع الجيدة لمراكمة الرصاص أكثر من القصب. This study aimed to study the accumulative abilities Ricnius Communis & Phragmites Communis for lead and cadmium. This plants are native near the RMAILAH river in JABLAH city. The plants samples were collected from leafs, wood, and bark for plant species, the soil samples were taken at (0-20)cm depth. Concentration of heavy metals were determined in soils and plants with "Atomic Absorption Spectrophotometer" Our results showed that the amounts of pb in the soil samples were 61.89ppm. The concentrations of lead pb in the parts of Ricnius Communis range between 4.3 to 5.81ppm; in the parts of Phragmites Communis range between 1.46 to 2.32ppm. According to statistics analysis Ricnius leaves surpass Ricnius wood and bark with accumulate lead; and Ricnius surpass Phragmites with accumulate lead too. Our results showed that the amounts of cd in the soil samples were 3.081ppm. The concentrations of Cd in the parts of Ricnius Communis range between 0.031 to 0.061ppm; in the parts of Phragmites Communis range between 0.031-0.055ppm. According to statistics analysis there is no moral differences between Ricnius and Phragmites with accumulate cadmium.